Non-specific effect of double-stranded RNAs on Egyptian broomrape (Phelipanche aegyptiaca) seed germination - Zainali, Nariman; Alizadeh, Houshang; Alizadeh, Hassan; Delavault, Philippe (Frontiers in Plant Science, 2025)
Obligate root parasitic plants of the Orobanchaceae family exhibit an intricate germination behavior. The host-dependent germination process of these parasites has prompted extensive research into effective control methods. While the effect of biomaterials such as amino acids and microRNA-encoded peptides have been explored, the effect of double-stranded RNAs (dsRNAs) has remained unexamined during the germination process. In this study, we asked whether an exogenously applied dsRNA can inhibit the germination of a root parasite, P. aegyptiaca. To this end, a dsRNA was designed to target the CYP707A1 (dsCYP7), a marker gene of the chemically-dependent germination of broomrape seeds. Application of a concentrated dsCYP7 significantly reduced seed germination. However, two non-germination-specific dsRNAs designed to target mannose-6-phosphate reductase and green fluorescent protein brought about similar inhibitions. Moreover, applying rNTPs and dNTPs, which mimic nitrogenous bases of nucleic acids, also caused a similar reduction in germination, suggesting that the non-specific inhibitory effect of the dsRNAs might arise from their nucleotides. While dsRNA application inhibited seed germination, their non-specific effects may pose a challenge for their application in studying root parasites germination. This underscores the importance of finding solutions to minimize the non-specific effects of dsRNAs to improve the potential of dsRNA as a tool to study and control root parasitic plants.